ChemInform Abstract: Recent Advances on the Application of NMR Methods to Study the Conformation and Recognition Properties of Carbohydrates. Issue 50 (10th December 2013) - Arda, Ana; Berbis, M. Alvaro; Blasco, Pilar; Canales, Angeles; Canada, F. Javier; Fernandez‐Alonso, M. Carmen; Marcelo, Filipa; Jimenez‐Barbero, Jesus
Abstract Review: 117 refs.